2019
DOI: 10.1080/13685538.2019.1643311
|View full text |Cite
|
Sign up to set email alerts
|

Glimpses into the molecular pathogenesis of Peyronie’s disease

Abstract: Peyronie's disease (PD) is a fibroproliferative disease of the penis. Since little is known about the molecular pathogenesis of PD, we compared the biochemical make-up of PD plaques with normal tunica albuginea to clarify pathological processes in the scarred tissue. Protein and mRNA levels were measured in plaques and in unaffected pieces of the tunica albuginea. We investigated the presence of myofibroblasts, the deposition of collagens, and some key elements of Wnt and YAP1 signaling at protein level. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
7
0
2
Order By: Relevance
“…Previous studies have shown that β-catenin is significantly upregulated in cells derived from PD plaque as compared to normal TA tissue [ 136 ]. Ten Dam et al performed immunostaining of PD plaque and normal TA tissues, and found significant upregulation of several WNT ligands in the PD samples, including WNT2, 4, 5a, and 7b, as well as β-catenin [ 137 ]. These results suggest that the activation of the WNT/β-catenin signaling pathway is associated with PD development.…”
Section: Core Signaling Pathways and Their Crosstalk Involved In Deve...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that β-catenin is significantly upregulated in cells derived from PD plaque as compared to normal TA tissue [ 136 ]. Ten Dam et al performed immunostaining of PD plaque and normal TA tissues, and found significant upregulation of several WNT ligands in the PD samples, including WNT2, 4, 5a, and 7b, as well as β-catenin [ 137 ]. These results suggest that the activation of the WNT/β-catenin signaling pathway is associated with PD development.…”
Section: Core Signaling Pathways and Their Crosstalk Involved In Deve...mentioning
confidence: 99%
“…Activation of hedgehog signaling is caused, at least in part, by TGF-β1 signaling, which induces transcription of the profibrotic Hedgehog transcription factor GLI family zinc finger 2 (GLI2) [ 144 ]. In addition, activation of Hedgehog signaling may upregulate Wnt-2b and Wnt-5a, shown to be overexpressed in PD, and may also activate WNT/β-catenin signaling [ 137 , 145 ].…”
Section: Core Signaling Pathways and Their Crosstalk Involved In Deve...mentioning
confidence: 99%
“…These studies generally focus on genetic, traumatic, and inflammatory processes. [17][18][19] However, regardless of the underlying cause, the inflammatory process that occurs later in the disease forms the basis of plaque formation. In the course of inflammation, Peyronie's disease occurs because of the production of inducible nitric oxide synthase (iNOS), which leads to an increase of nitric oxide and a corresponding increase in the production of peroxynitrite anion.…”
Section: Discussionmentioning
confidence: 99%
“…The average IIEF-5 score before treatment was 18.1 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). This score increased to 20.2 (10-25) after treatment.…”
Section: Re Sultsmentioning
confidence: 97%
“…Peyronie’s disease (PD) is a benign condition characterized by the formation of fibrous plaque in the tunica albuginea layer of the penis. 1 , 2 It is an important condition that can cause painful penile erection, curvature deformity in the penis, shortened penile length, erectile dysfunction, and associated psychological problems. 3 , 4 The prevalence of PD varies between 0.4% and 23% in different case series.…”
Section: Introductionmentioning
confidence: 99%